2015
DOI: 10.1371/journal.pone.0120221
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling the Interaction between Quinolinate and the Receptor for Advanced Glycation End Products (RAGE): Relevance for Early Neuropathological Processes

Abstract: The receptor for advanced glycation end products (RAGE) is a pattern-recognition receptor involved in neurodegenerative and inflammatory disorders. RAGE induces cellular signaling upon binding to a variety of ligands. Evidence suggests that RAGE up-regulation is involved in quinolinate (QUIN)-induced toxicity. We investigated the QUIN-induced toxic events associated with early noxious responses, which might be linked to signaling cascades leading to cell death. The extent of early cellular damage caused by thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 74 publications
(101 reference statements)
2
17
0
1
Order By: Relevance
“… e RAGE-Aβ model complex predicted by protein–protein docking software reported in ref ( 83 ). f Binding mode of quinolinic acid and RAGE VC1 domain predicted by computational docking in ref ( 87 ). …”
Section: Extracellular Rage Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“… e RAGE-Aβ model complex predicted by protein–protein docking software reported in ref ( 83 ). f Binding mode of quinolinic acid and RAGE VC1 domain predicted by computational docking in ref ( 87 ). …”
Section: Extracellular Rage Ligandsmentioning
confidence: 99%
“… f Binding mode of quinolinic acid and RAGE VC1 domain predicted by computational docking in ref ( 87 ). …”
Section: Extracellular Rage Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that this SAC-related garlic derived compound possesses important antiglycative properties, but once again, this effect deserves additional confirmation in living systems. Supporting evidence on a real protective role of SAC on the AGEPs-related damaging signaling has been recently published by our group through an in vivo approach involving the receptor for AGEPs, RAGEP (Serratos et al, 2015). The dimeric transmembrane RAGEP protein is involved in triggering different signaling cascades leading to cell damage once it is stimulated by AGEPs.…”
Section: Sac Advanced Glycation End Products (Ageps) and The Receptomentioning
confidence: 86%
“…Rage is a receptor-transporter system that can binds to many ligands and activates many pathways. Disturbances in Rage have been linked to many inflammatory and neurodegenerative disorders like Huntington's disease(Serratos et al, 2015). BBB disruption does not occur in all cases of neurodegeneration.…”
mentioning
confidence: 99%